Abertura econômica, eficiência técnica e produtividade total dos fatores do Brasil e América Latina - Abreu, Carla Cintia Andrade de (2018)
This thesis is composed of three articles. The first article analyzes the trajectory of the Brazilian economic openness, from 1950 to 2010. For this analysis, the unit root test with structural break shown by Saikkonen and Lütkepohl (2002) and Lanne et al. (2002) is used. In addition, the Bai and Perron (1998) test is performed to verify the result found with the first test. Both tests indicated that there was a structural break in 1993. The second article examines the variation of the total factor productivity (TFP) of a sample of 19 Latin American countries, from 1960 to 2010. For this analysis, the stochastic frontier model proposed by Pitt and Lee (1981) is used, and the term of technical inefficiency was modeled according to the model proposed by Battese and Coelli (1995). From the estimation of the econometric model, it is possible to find the sources of technical inefficiency in the production. For the calculation of the TFP variation and its decomposition, two methodologies are used: the Malmquist (1953) index and the technique proposed by Bauer (1990) and Kumbhakar (2000). Using the Malmquist total productivity index, productivity growth is broken down into two components: technological variation and technical efficiency variation. This decomposition procedure allows identifying and quantifying the determinants of TFP performance over time: the component that explains an approximation of the production frontier (variation of technical efficiency) and that related to the displacement of the production frontier itself (technological variation). Using the technique proposed by Bauer (1990) and Kumbhakar (2000), productivity can be decomposed in other terms beyond the variation of technical efficiency and technological variation. Through this, the total factor productivity is broken down into technical progress, technical efficiency, gains in scale and allocative gains. Among other conclusions, the most relevant is that the performance of total factor productivity was the main reason for the low economic growth in Latin America in the period studied. The third article shows the evolution of the total factor productivity of the Brazilian economy in the period from 1960 to 2010. As a result, the performance of total factor productivity was the main reason for Brazil's low economic growth in the period studied.